Iron supply of enterococci by 2-oxoacids and hydroxyacids - Lisiecki, Paweł; Mikucki, Jerzy (Polish journal of microbiology, 2006)
Only 9 (11.2%) out of 80 studied bacterial strains were able to utilize iron saturated 2-oxo acids and hydroxyacids and grow on o-phenantroline containing media. These strains belonged to Enterococcus faecalis and Enterococcus faecium species and were isolated from clinical material. Iron sources utilized by all of these strains were Fe(III) complexes with pyruvic, 2-oxobutyric, 4-methylthio-2-oxobutyric, 2-oxo-3-methylvaleric, 2-oxoisocaproic and 2-oxoadipic acids. None of the nine strains released 2-oxoacids to environment during growth in iron excess Fe+ medium and iron deficient--Fe- (Chelex) medium. In Fe- (phenantroline) medium, when the growth was strongly inhibited, only pyruvic acid was released. Iron uptake from 59Fe(III)-pyruvate was depended on iron deficiency during growth: cells harvested from Fe- (phenantroline) medium have acquired the most amount of iron. 2,4-Dinitrofenol was a strong inhibitor of 59Fe(III) iron uptake. Release of pyruvic acid is not subject to negative derepression and does not require the presense of iron as its inductor. It appears in the environment as a response to growth inhibiting stress caused by the iron deficiency but contrary to siderophores are not specially synthesized for iron assimilation. Therefore, it is only primary metabolism products released by damaged, but metabolic active cells.